X+y = 42
x-y = 8
x = 8+y
Substitute it in 1st equation,
8+y+y=42
2y = 34
y = 17
Substitute it in 1st eq.,
x = 42-17 = 25
So, the two numbers are 25 & 17
Hope this helps!
Answer:
5% decrease
Step-by-step explanation:
L = liz's age now
J = Jack's age now
L-1 and J-1 are their ages one year ago
L-1=3(J-1)
L-1=3J-3
L=3J-3+1
L=3J-2 (to be used later)
L+2 and J+2 are their ages in two years
L+2=2(J+2)
replace L by 3J-2
3J-2+2=2(J+2)
3J=2J+4
3J-2J=4
J=4 is Jack's age now
L-1=3(J-1)
L-1=3(4-1)
L-1=3*3
L-1=9
L=9+1
L=10 is Liz's age now
Answer:
It means <u>what is the y-value of the given function, if 0 is substituted in for x.</u>
Hope this helps!